Comparison of functional outcome of extra-articular distal radius fractures treated by volar locking plate versus percutaneous pinning in adults-a retrospective study - Bhavi, Shushrut B.; Kallanagoudar, Amith Shanmukgouda; Kaladagi, Deepak; Sanakal, N. B. (International Journal of Research in Orthopaedics, 2021)
Background: Distal radius fractures are one of the most common fractures in an adult population and accounts for 17.5% of all the fractures. The management of distal radius fractures remains debatable despite the availability of different methods of treatment. The aim of this study is to assess the functional outcomes of extra-articular distal radius fractures treated with percutaneous pinning or internal fixation with volar locking plate in adults. Methods: A retrospective study of 40 patients diagnosed with distal radius fracture with AO classification were treated either with percutaneous pinning (n=20) or open reduction and internal fixation with volar locking plate (n=20) were included in study. DASH score and radiographs at 6th month was assessed for functional outcome and radiological union. Results: Mean age in plate group was 40 and 45 years in K wire group. The mean passive wrist ROM at the final follow-up evaluation in plate group was 63.8o extension and 70.5o flexion, 81.7o supination and 79o pronation, compared with 56.75o extension and 65.25o flexion, 74.7o supination and 85.5o pronation in patients treated with K wire group. Patients with plate group and K wire group had DASH score of 19.85 and 18.49 respectively (p=0.07) at 6 months follow-up. Conclusions: The use of ORIF with plate resulted in stable fixation of the unstable extraarticular fractures, allowing early post-surgical wrist motion and has good radiological outcome whereas K wire also has advantages of being minimal invasive, reduced hospital stay and minimal cost.